Genome localization of adeno-associated virus RNA. - Carter, B J (1976)
In previous work, linear duplex molecules of adeno-associated virus, type 2 (AAV2), DNA were cleaved with the restriction endonucleases R-EcoRI, R-HindII, and R-HindIII. The physical order of the specific fragments obtained was deduced and oriented with respect to the DNA strand polarity and the direction of transcription. Stable AAV RNA is transcribed only from 70% of the minus DNA strand. We report here RNA-DNA hybridization experiments using these restriction fragments to obtain a more accurate map of the portion of the AAV genome represented in stable RNA. The data obtained with several sets of restriction fragments annealed to either whole-cell RNA or poly(A)-containing RNA were internally consistent. The AAV RNA annealed with a continuous region of the AAV DNA, beginning at 0.18 map units (18%) from the left end of the molecule and ending at 0.88 map units. In addition, the restriction endonuclease BamHI was found to make one specific cleavage in AAV2 DNA at 0.22 map units, which is 0.04 map units (i.e., 160 nucleotides) to the right (""down stream'') of the point corresponding to the 5' end of the viral mRNA.